Akselerasi kemandirian pesantren melalui pelaksanaan unit usaha santri - Olis; Wahidin (STAI Kuala Kapuas, 2024)
This article discussed the implementation of santri cooprative units at pesantren, to improve the character of empowered pesantren. The method used in this study was a qualitative library research type approach, data collection tehniques used literature studies in the form of articles, newspaper, notes and internet. The result obtained from this study was a through education and training, management of the santri cooprative units, the role of kiyai and the principles of cultural values in the organization of the santri coopratvie unit at pesantren.